Metakognisi Siswa Operasional Konkret Dalam Pemecahan Masalah Matematika - Mu'jizatin Fadiana; Andriani Andriani (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
Vocational High School students should have their cognitive development stage in formal operations. However, there are still vocational high school students whose cognitive development stages are in concrete operations. The purpose of this study was to determine the students' concrete operational metacognition in solving mathematical problems. The research method used is descriptive qualitative. The research subjects were two students who were taken using purposive sampling. The research instrument used was the logical thinking ability test, problem-solving tests and metacognition interview guidelines. The data analysis stages used were examining all data, classifying the level of students' logical thinking abilities, selecting concrete operational students to be used as research subjects, reviewing the results of concrete operational student metacognition work in solving mathematical problems, verifying data and data sources that had been classified and transcribed in presentation or exposure to data. The results showed that concrete operational students carried out cognitive regulation in the step of understanding problems, implementing plans and re-examining solutions that had been produced. The metacognition skill component appeared at all three steps. Only the step of making a plan that does not occur properly regulation of cognition. It can be concluded that concrete operational students who are in grade X of vocational high school have good metacognition skills, but are weak in problem solving abilities.